Seismic Evidence for Plume‐ and Craton‐Influenced Upper Mantle Structure Beneath the Northern Malawi Rift and the Rungwe Volcanic Province, East Africa. (25th October 2018) - Grijalva, Ashley; Nyblade, Andrew A.; Homman, Kyle; Accardo, Natalie J.; Gaherty, James B.; Ebinger, Cynthia J.; Shillington, Donna J.; Chindandali, Patrick R. N.; Mbogoni, Gabriel; Ferdinand, Richard Wambura; Mulibo, Gabriel; O'Donnell, J. P.; et al.
Abstract: P and S wave tomographic models have been developed for the northern Malawi rift and adjacent Rungwe Volcanic Province (RVP) using data from the Study of Extension and maGmatism in Malawi aNd Tanzania project and data from previous networks in the study area. The main features of the models are a low‐velocity zone (LVZ) with δ Vp  = ~−1.5–2.0% and δ Vs  = ~−2–3% centered beneath the RVP, a lower‐amplitude LVZ (δ Vp  = ~−1.0–1.3% and δ Vs  = ~−0.7–1%) to the southeast of the RVP beneath the center and northeastern side of the northern Malawi rift, a shift of the lower‐amplitude anomaly at ~−10° to −11° to the west beneath the central basin and to the western side of the rift, and a fast anomaly at all depths beneath the Bangweulu Craton. The LVZ widens further at depths >~150–200 km and extends to the north beneath northwestern Malawi, wrapping around the fast anomaly beneath the craton. We attribute the LVZ beneath the RVP and the northern Malawi rift to the flow of warm, superplume mantle from the southwest, upwelling beneath and around the Bangweulu Craton lithosphere, consistent with high 3 He/ 4 He values from the RVP. The LVZ under the RVP and northern Malawi rift strongly indicates that the rifted lithosphere has been thermally perturbed. Given that volcanism in the RVP began about 10 million years earlier than the rift faulting, thermal and/or magmatic weakening of the lithosphere may have begun prior to the onset of rifting. Plain Language Summary: P and S wave tomographic models have been developed for the northern Malawi rift and adjacent Rungwe Volcanic Province (RVP) using data from the Study of Extension and maGmatism in Malawi aNd Tanzania project and data from previous networks in the study area. A low‐velocity anomaly is imaged under the RVP and northern Malawi rift. We attribute the low‐velocity anomaly to flow of warm mantle from the African superplume to the southwest of the study area, which has migrated around the side of thick Bangweulu Craton lithosphere and upwelled beneath the thinner mobile belt lithosphere to the east of the Bangweulu Craton. The observation that volcanism began in the RVP prior to the onset of rifting suggests that the lithosphere beneath the Malawi rift may have been thermally weakened prior to rifting. Key Points: Low‐velocity anomaly is imaged under Rungwe Volcanic Province and northern Malawi rift Low‐velocity anomaly is attributed to upwelling of warm mantle around side of Bangweulu Craton lithosphere Lithosphere beneath the Malawi rift may have been weakened prior to rifting